2019
DOI: 10.1111/ans.15475
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorne effect on surgical studies

Abstract: Background The Hawthorne effect or ‘observer effect’ describes a change in normal behaviour when individuals are aware they are being observed. This may have an impact on effect estimates in clinical trials. The purpose of this study was to determine if the Hawthorne effect had been recorded as a risk of bias in surgical studies. Methods A Preferred Reporting Items for Systematic Reviews and Meta‐Analyses compliant literature search was conducted till March 2019. Eligible studies included those reporting or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 31 publications
(150 reference statements)
2
24
0
Order By: Relevance
“…Furthermore, since the trainer was observing the practices, Hawthorne effect cannot be ruled out. [39] However, as seen in our results, even though the practices improved, some of them did not improve as much as others. The mean age in our study was 25.9; hence there may be concerns that the population of nurses included in the study is relatively young.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, since the trainer was observing the practices, Hawthorne effect cannot be ruled out. [39] However, as seen in our results, even though the practices improved, some of them did not improve as much as others. The mean age in our study was 25.9; hence there may be concerns that the population of nurses included in the study is relatively young.…”
Section: Discussionsupporting
confidence: 50%
“…It has been shown previously that in addition to directly comparing between hospitals, self-evaluation leads to an increase in quality in individual hospitals, which is referred to as the Hawthorne effect [ 26 ]. The morbidity and mortality in participating hospitals decreased significantly due to the introduction of NSQIP [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This would not be the case if the study had omitted evaluations during routine working in the operating theatre. Simulated assessments have been shown to offer a reasonably good reflection of performance in the real world 39 . In addition, as SCS is a subjective process, subjective assessment needed to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as SCS is a subjective process, subjective assessment needed to be considered. A Hawthorne effect—the temporary alteration of behaviour by the subjects of a study owing to their awareness of being observed—cannot be discounted 39 .…”
Section: Discussionmentioning
confidence: 99%